(3GdYRj aj GdJUQjas - (3GdNRQLj GdnqRrfLGfj, GdYRj (B((3YR GdOjf(B)(3, YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH, J (B655 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg(B...(3CeG HYO GYde Cf GdJUQja aj GddZI(B...s
(3BNQgG (B:s
...(3hGdaYdI HGdcSQI ddfhY ef GdaYd Jbhd gh MSf GdWYeI hGdLdSI hGdQcHI(B...s
(3JHUQI GdeDda (B:s
(3haj eYLe GdeDdajf(B: (3GSeg EHQGgje Hf YHO GdhgGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B179s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B42s
(3cTa GdXfhf(B:(3L(B2(3,U(B1138s
Keywords: (3GdUQas